2007
DOI: 10.1111/j.1600-0579.2007.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Video‐assisted clinical instruction in dentistry. Overview and applications

Abstract: Dental education can benefit from adopting new technologies and modern learning practices. Video-assisted clinical instruction in dentistry (VACID) uses video technology with the purpose of enhancing the teaching of technical skills and the acquisition of clinical knowledge, as well as fostering student-centered learning and critical self-appraisal. VACID is made possible through the capturing, recording, transmitting and viewing of high quality video images of live or pre-recorded clinical procedures. As such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 21 publications
(23 reference statements)
1
21
0
Order By: Relevance
“…Furthermore, the findings of our study are consistent with previous research in dental education and other disciplines that found support for the use of videos as an adjunct to classroom teaching. 11,[17][18][19]21,[24][25][26][27][28][29][30] Our findings suggest dental hygiene instrumentation videos can be successful in improving learning by meeting the needs of students to supplement traditional teaching of clinical skills.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, the findings of our study are consistent with previous research in dental education and other disciplines that found support for the use of videos as an adjunct to classroom teaching. 11,[17][18][19]21,[24][25][26][27][28][29][30] Our findings suggest dental hygiene instrumentation videos can be successful in improving learning by meeting the needs of students to supplement traditional teaching of clinical skills.…”
Section: Discussionmentioning
confidence: 98%
“…10 While instrumentation videos are a relatively new adjunct to teaching dental hygiene instrumentation skills to students, the use of video as an instructional aid has been widely studied in health professions education. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Holland et al found that online video was an effective instructional method for nursing students in developing clinical skills. 11 Other studies reported that using video as a pedagogic tool increased engagement of nursing students and provided useful conceptual links between theory and practice.…”
mentioning
confidence: 99%
“…15 However, other studies questioned the capability of conventional learning methods in offering a more in-depth learning experience for students and suggest that more simulation and innovative learning methods would improve educational outcomes in periodontics. [16][17][18][19][20] Nonetheless, despite reports about the positive effects of TEL in improving educational outcomes in periodontics education, 13,[21][22][23] Ramlogan et al highlighted that the exclusive use of video as a TEL had some limitations. 12 Furthermore, corroborating with Levine et al, some authors did not find a difference in TEL application to traditional learning methods in improving educational outcomes of undergraduate dental students' in periodontics.…”
Section: Introductionmentioning
confidence: 99%
“…Video assisted learning has become an integral part of effective teaching. 5 Using procedural or instructional videos have shown to augment student's preparedness for real life clinical practice and helps them to improve their skills at their own pace and learning ability. 6 It helps in better visualization and offer simulation in variety of learning styles according to a student's preference and can be saved to be repeated multiple times.…”
Section: Introductionmentioning
confidence: 99%